Comparison of nine theoretical models for estimating the mechanical power output in cycling - Gonzalez-Haro, C.; Ballarini, G.; Soria, M.; Drobnic, F.; Escanero, J. F. (British Journal of Sports Medicine, 2007)
Objective: To assess which of the equations used to estimate mechanical power output for a wide aerobic range of exercise intensities gives the closest value to that measured with the SRM training system.